Curcumin and Related Compounds in Cancer Cells: New Avenues for Old Molecules - Costantino, Matteo; Corno, Cristina; Colombo, Diego; Perego, Paola (Frontiers in Pharmacology, 2022)
Curcumin and related compounds are known for the large spectrum of activities The chemical features of these compounds are important for their biological effects with a key role for the thiol-reactive  unsaturated carbonyl groups. Curcumin derivatives may overcome the limitation of the bioavailability of the parent compound, while maintaining the key chemical features responsible for biological activities. Curcumin and related compounds show anti-viral, anti-fungal, anti-microbial and anti-tumor activities. The therapeutic effects of curcumin, used as a supplement in cancer therapy, have been documented in various cancer types, in which inhibition of cell growth and survival pathways, induction of apoptosis and other cell death pathways have been reported. Curcumin-induced apoptosis has been linked both to the intrinsic and extrinsic apoptotic pathways. Necroptosis has also been involved in curcumin-induced toxicity. Among curcumin-induced effects, ferroptosis has also been described. The mechanism of curcumin toxicity can be triggered by reactive oxygen species-mediated endoplasmic reticulum stress. Curcumin targets have been identified in the context of the ubiquitin-proteasome system with evidence of inhibition of the proteasome proteolytic activities and cellular deubiquitinases. Curcumin has recently been shown to act on the tumor microenvironment with effects on cancer-associated fibroblasts and immune cells. The related product caffeic acid phenethyl ester has shown promising preclinical results with an effect on the inflammatory microenvironment. Here, we review the mechanisms underlying curcumin and derivatives toxicity towards cancer cells with particular emphasis on cell death pathways and the ubiquitin-proteasome system.